Desempenho de protótipos de disco para distribuição de ureia a lanço - Brondani, Leonardo Basso (2013)
The correct use and distribution of correctives and fertilizers on growth areas, setting right the soil or returning the nutrients exported by the crops, is one of the most important techniques to increase and maintain the agricultural income. The centrifugal broadcasters of solid products are increasingly used because of its practicality, simplicity and high operational capacity. Its main use is on the application of corrective and fertilization products of agricultural soils, which can apply calcareous, agricultural gypsum, mineral fertilizer and, once these resources are finite, they demand a rationalization on the use and, as a consequence, the correct application becomes indispensable. The development of virtual prototypes has been a great successful and reliable tool in the last years, offering the opportunity to verify the viability of a prototype by simulation without the need to build it. In this context, the present study intent to evaluate the real behavior of projected prototypes in track conditions compared with a conventional disk. The prototypes used in search were developed in a master thesis of the Postgraduate Program in Agricultural Engineering by the academic Mech. Eng. Elton Neves da Silva. Based on the graphics of distribution analyzes obtained from the simulations, it was chosen for the prototypes called Conic 6 Wings Middle and Plan 6 Wings Middle, which were the ones that presented the best results. The observations demonstrated that the width of work for a conventional disc, in the position 50% of wings course, was the one that presented a higher value, getting to 25 meters, in a right alternate system. The Conic prototype presented, for the CV of 15%, a width inferior to 10 meters, independent of the work method used, and the Plan prototype presented the smallest value of work width, getting, at maximum, 7,5 meters for the CV stipulated of 15%. At the evaluation of the longitudinal profile of distribution, as for the conventional disc in three positions as for the Conic and Plan prototypes, both presented a uniformity of distribution. In comparison between the conventional disc and the prototypes, the conventional disc revealed better results for all the work methods.